Experimental and Finite Element Investigation of Composite Beams Consisting of Reinforced Concrete Prisms Cast Into Steel Channels - Al-Hadithy, Laith Khalid; Al-Kerbooli, Omer Khalid (Nahrain University College of Engineering Journal, 2008)
Four reinforced concrete beams of rectangular crosssections and four corresponding composite ones consisting of reinforced concrete prisms cast into steel channels with shear connectors were manufactured, loaded, and tested in the laboratory to measure mid-span deflections, and to observe fracture criteria. The reinforced concrete prism of each of the four composite beams is of rectangular ross-section and identical to its corresponding reinforced concrete beam.Load-deflection behavior and fracture pattern at failure obtained experimentally for each of the eight beams were compared with those predicted by a nonlinear three-dimensional finite element analysis using the analysis system computer program (ANSYS V. 5.4) in which the reinforced concrete, the steel channel, and the interaction between reinforced concrete and steel channel were modeled by isoparametric eight-node brick elements, four-node shell elements ,and the five-node interface elements ,respectively. High agreement between the experimental tests and the numerical models was obtained for loaddeflection behavior represented by maximum differences of 11% and 7% for composite and noncomposite beams, respectively. In addition, a perfect coincidence in predicting fracture pattern at failure by the two methods was realized. Comparisons between flexural behaviors for each of the present four pairs of correspondent composite and non-composite beams show that introducing the integrated steel channels highly increases the ultimate load capacity by 155% to 500% -depending on the ratio of steel channel area to gross concrete area, and decreases the ductility ratio by 26.4% to 36.7% - depending on the ratio of steel channel area to tension reinforcement area. A parametric study on the effect of flange width of the steel channel show that a 40% increase in the ultimate load capacity can be realized by a one-third increase in that parameter with a slight decrease in ductility ratio.